2021
DOI: 10.3389/fphar.2021.684550
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E for the Prevention of Chemotherapy-Induced Peripheral Neuropathy: A meta-Analysis

Abstract: Background: Vitamin E has been increasingly used to prevent chemotherapy-induced peripheral neuropathy (CIPN) in recent years. However, it is still unclear whether vitamin E can effectively prevent CIPN.Methods: We searched all clinical studies in the Embase, Cochrane Library, Clinicaltrials.gov, and PubMed databases from inception to December 2020. We performed a meta-analysis of 9 randomized controlled trials (RCTs) with 486 patients that compared the vitamin E group with the control group. Outcomes of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…However, the findings of our current review were based on a study supplementing Omega-3 PUFA in an oral nutrition supplement drink [37]. Therefore, it cannot be confirmed whether the beneficial effects on CIPN resulted from Omega-3 PUFA or one or a combination of other nutrients with known benefits on nerve functioning and suggested modest benefits on CIPN in other cancer populations, such as amino acids, B vitamins, vitamin E, and magnesium [16,[50][51][52]. Our current review did find additional potential benefits of the amino acid glutamine for CIPN in advanced cancer populations [38].…”
Section: Discussionmentioning
confidence: 77%
“…However, the findings of our current review were based on a study supplementing Omega-3 PUFA in an oral nutrition supplement drink [37]. Therefore, it cannot be confirmed whether the beneficial effects on CIPN resulted from Omega-3 PUFA or one or a combination of other nutrients with known benefits on nerve functioning and suggested modest benefits on CIPN in other cancer populations, such as amino acids, B vitamins, vitamin E, and magnesium [16,[50][51][52]. Our current review did find additional potential benefits of the amino acid glutamine for CIPN in advanced cancer populations [38].…”
Section: Discussionmentioning
confidence: 77%
“…They used these NPs for cytoprotection against cisplatin. The succinate form of α-TOS can prevent apoptosis caused by cisplatin due to its ability to monopolize the mitochondria respiratory chain, regulate ROS production, decrease caspase 3/7 activity, and release IL-1 ( 26 ). Cytotoxicity of DEX-loaded and α-TOS-loaded NPs was tested using HEI-OC1, and the results demonstrated that only the highest concentration (2.0 mg/ml) of DEX-NP was cytotoxic after 24 h (viability < 70%).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Zudem gab es auch keinen signifikanten Unterschied in der Häufigkeit schwerer tumortherapieassoziierter Neuropathien zwischen beiden Gruppen. Die routinemäßige prophylaktische Einnahme von Vitamin E empfehlen wir daher aktuell nicht, bis entsprechend Daten aus weiteren doppelblind randomisierten klinischen Studien, die die präventive Wirkung von Vitamin E untersuchen, vorliegen [ 10 ].…”
Section: Peripheres Nervensystem Und Muskulaturunclassified
“…Die therapieassoziierten Myopathien, die unter Immuncheckpoint-Inhibitoren (z. B. PD-1-Antikörper oder CTLA4-Antikörper) oder unter dem Proteinkinaseinhibitor Imatinib oder dem MEK1/2(„mitogen activated protein kinase 1 and 2“)-Inhibitor Selumetinib auftreten, können allerdings auch die Rumpfmuskulatur
Rumpfmuskulatur
betreffen [ 10 ], daher ist eine sorgfältige klinische Evaluation von entscheidender Bedeutung für eine zielführende (Differenzial‑)Diagnose.…”
Section: Peripheres Nervensystem Und Muskulaturunclassified